1970
DOI: 10.1366/000370270774371534
|View full text |Cite
|
Sign up to set email alerts
|

A Detailed Study of Lead Determinations in Air-Borne Particulates over Morton Grove, Illinois by Atomic Absorption Spectroscopy

Abstract: Careful examination of an analytical method for the determination of lead concentrations in atmospheric particulates has confirmed that a low temperature ashing technique is preferable to the ashing of organic matter in a muffle furnace when preparing samples for metals analysis, and that use of the standard additions technique for the avoidance of interferences in the analyses by atomic absorption spectroscopy is justified. Analyses of some 600 samples collected from the air over Morton Grove, Illinois from 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

1971
1971
1989
1989

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 8 publications
0
4
1
Order By: Relevance
“…Atomic Absorption Interferences. Our spike recovery data of 93% with 9% RSD do not support the large interferences found by Burnham et al (3) on the 283.3-nm line with their Illinois samples. The agreement of our atomic absorption and optical emission data (obtained with the 220.4-nm line) in general and the spike recovery data in particular proves that no significant atomic absorption interferences occurred with these samples from widely distributed sites across the United States.…”
Section: Table I Emission Spectrometer and Excitation Conditionscontrasting
confidence: 99%
“…Atomic Absorption Interferences. Our spike recovery data of 93% with 9% RSD do not support the large interferences found by Burnham et al (3) on the 283.3-nm line with their Illinois samples. The agreement of our atomic absorption and optical emission data (obtained with the 220.4-nm line) in general and the spike recovery data in particular proves that no significant atomic absorption interferences occurred with these samples from widely distributed sites across the United States.…”
Section: Table I Emission Spectrometer and Excitation Conditionscontrasting
confidence: 99%
“…The determination of trace metals in particulate matter by atomic absorption spectrometry (aas) (Morgan and Homan, 1967;West, 1968) usually involves the initial destruction of organic matter in the sample followed by acid dissolution of residues. Dry ashing at high temperatures, as a method of oxidizing organic matter on glass filters, has been ruled out by some investigators (Burnham et al, 1969(Burnham et al, , 1970; Kneip et al, 1970;Morgan and Homan, 1967) because of the observed losses of low-melting metals. The most frequent explanation offered for these losses has been the volatilization of metals at high temperatures.…”
mentioning
confidence: 99%
“…In recent years, atomic absorption spectrometry has been used in the analysis of trace metals in atmo- spheric particulates (21)(22)(23)(24)(25)(26)(27). Chief reasons for this trend include less sample preparation, selectivity, sensitivity, and relatively simple operating techniques.…”
Section: Methods Of Analysismentioning
confidence: 99%